2003
DOI: 10.1007/s00204-002-0417-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive impairment in Japanese quail (Coturnix japonica) after in ovo exposure to o,p'-DDT

Abstract: We have previously described various effects in adult Japanese quail consequent on treatment with oestrogenic compounds in ovo. In the present study, the environmental contaminant o,p'-DDT [1-(2-chlorophenyl)-1-(4-chlorophenyl)-2,2,2-trichloroethane] was administered to quail eggs to further evaluate test endpoints for oestrogenic effects related to reproduction in the Japanese quail. Exposure to 2 mg o,p'-DDT/egg (150 micro g/g egg) resulted in impaired sexual behaviour, reduced cloacal gland area and lowered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 28 publications
5
30
1
1
Order By: Relevance
“…Consequently, the permanent effects of the estrogen like compounds on sexual behavioral can be induced by administering during a sensitive developmental stage, such as the period of differentiation or maturation of the reproductive organs (Panzica et al, 2009). Whereas estrogen-induced morphological changes in the testis have been reported to disappear after hatching (Halldin et al, 1999(Halldin et al, , 2003 while the estrogen-induced effects on the male brain are rather permanent. Generally, it can be suggested that effects of high doses of BPA in pubertal males is expected to be irreversible when the pollutant chemical is existent elongated enough during the period of instigation of sexual behavior (Panzica et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the permanent effects of the estrogen like compounds on sexual behavioral can be induced by administering during a sensitive developmental stage, such as the period of differentiation or maturation of the reproductive organs (Panzica et al, 2009). Whereas estrogen-induced morphological changes in the testis have been reported to disappear after hatching (Halldin et al, 1999(Halldin et al, , 2003 while the estrogen-induced effects on the male brain are rather permanent. Generally, it can be suggested that effects of high doses of BPA in pubertal males is expected to be irreversible when the pollutant chemical is existent elongated enough during the period of instigation of sexual behavior (Panzica et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Using highly conserved primers flanking the intron of the gene, PCR amplification and agarose electrophoresis, 47 out of 50 bird species were successfully sexing 17 , whereas the method did not provide complete results and spent considerable cost and time. On the other hand, in ovo exposure of EDCs is the most important route in the birds [1][2][3]11 and avian eggs have been elucidated to be a good test system for evaluating effects of EDCs 5,[12][13][14][18][19][20][21][22] . Maternal transfer of 17 beta-estradiol benzoate (EB) to egg yolk has been demonstrated in Japanese quail, in which female quails received EB in the routs of i.m.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, Gray et al (1982) observed a decrease in testicular weight. Embryonic exposure to xenoestrogens produced a reduction in the growth of the cloacal gland at sexual maturity in male Japanese quail (Adkins, 1979;Halldin et al, 1999;Halldin et al, 2003). This effect may be induced by activation of ERα since propyl pyrazol triol (PPT) treatment during quail embryo development significantly reduced the cloacal gland area in sexually mature males (Mattsson et al, 2008b).…”
Section: Effects On Histopathologymentioning
confidence: 99%